Chemical modifications of diphenyl diselenide enhance its anti-Sporothrix spp. activity and exhibit synergism with itraconazole - Jéssica Estefania Dávila Hidalgo; Melissa Orzechowski Xavier; Mariana Rodrigues Trápaga; Beatriz Cardoso; Mônica Campos dos Santos; Diulien Canary; Gilson Zeni; Cristina Wayne Nogueira; Rodrigo Almeida-Paes; Rosely Maria Zancopé-Oliveira; Vanice Rodrigues Poester (Brazilian Journal of Microbiology, 2026)
Sporotrichosis is a globally distributed subcutaneous mycosis caused by fungi belonging to the Sporothrix genus. The limitations of current treatment options for sporotrichosis have driven an urgent search for new antifungal drugs. Diphenyl diselenide (PhSe)₂, a stable organoselenium, has promising activity against Sporothrix spp. Since chemical modifications in molecules can enhance their antifungal properties, this study aimed to evaluate the anti- Sporothrix activity of two analogs of (PhSe)₂—p-methoxyl-diphenyl diselenide (BMD) and bis-(3-trifluoromethylphenyl) diselenide (CF3)—both alone and in combination with itraconazole (ITZ). A total of 25 Sporothrix spp. isolates ( S. brasiliensis n = 20; S. schenckii n = 4 and S. globosa n = 1) were included. The microdilution and checkerboard assays were used to assess its antifungal activity alone and in combination, respectively. BMD inhibited all isolates, with a total minimum inhibitory concentration ranging from 2 to 16 µg/mL. In contrast, CF3 exhibited only a partial minimum inhibitory concentration activity in 92% of isolates at concentrations ranging from 2 to 16 µg/mL. When combined with ITZ, both compounds predominantly exhibited a synergistic effect (100% for BMD and 73% for CF3). Our study presents pioneering data on two organoselenium compounds with significant in vitro activity against the main pathogenic Sporothrix species, both alone and in combination with ITZ. Further studies are needed to determine whether these in vitro findings translate into in vivo efficacy.